Mitral Intervention with LVAD: Preparing for Recovery. (March 2019) - Maxwell, Cory; Whitener, George
Left ventricular assist device (LVAD) insertion is an increasingly common treatment of advanced heart failure. Insertion guidelines suggest regurgitant lesions of the mitral valve should not be addressed. However, recent evidence suggests that mitral regurgitation may not necessarily improve with LVAD insertion, and such patients may have worse outcomes. Thus, practice variability is high given the discrepancy between traditional thinking and new evidence that unrepaired mitral regurgitation may increase perioperative mortality. Additionally, the challenges of LVADs can make transesophageal echocardiography evaluation and assessment of mitral valve pathology difficult.